Exploring the utility of near-infrared spectroscopy in liver transplantation: insights and challenges - Ravshan Ibadov; Konstantin Semash; Mirshavkat Akbarov; Timur Dzhanbekov; Oybek Omonov; Azimjon Usmonov; Sardor Ibragimov (Clinical Transplantation and Research, 2025)
Maintaining adequate tissue perfusion and oxygen delivery to the transplanted liver is critical for positive patient outcomes. Near-infrared spectroscopy (NIRS) has emerged as a promising tool for evaluating graft function in liver transplantation, particularly in assessing tissue perfusion. This review consolidates current knowledge regarding the application of NIRS in liver transplantation, highlighting its potential for noninvasive, continuous monitoring of liver perfusion and early detection of hemodynamic disturbances. Initial studies demonstrate the sensitivity of NIRS in evaluating liver oxygenation, with significant correlations observed between NIRS readings and biochemical markers of liver function. However, the effectiveness of NIRS can be influenced by factors such as subcutaneous fat thickness and patient positioning. Recent advancements also suggest that NIRS may assist in predicting graft fibrosis and other longterm complications. More extensive studies are required to establish standardized protocols and validate the clinical utility of NIRS in liver transplantation.